Topographical and chemical characterisation of temperature controlled on-surface reactions - Clarke, Michael Peter (2025)
On-surface synthesis, the process of producing covalently bonded structures from molecular building blocks confined on a surface, is a research theme worthy of investigation as it offers a route towards the fabrication of nanoscale two-dimensional devices. Alongside the potential applications within the burgeoning field of nanoelectronics, confining materials to surfaces allows the use of a variety of surface analysis techniques. Scanning probe microscopy, for example, can reveal with unrivalled detail mechanistic information about the progress of reactions in general. Developing our understanding of these processes can allow for the formation of more precise and complex structures ‘on-surface’ and may pave the way for developing new methodologies within solution phase synthesis.